Effective potential of interactions between ions in dense quantum plasmas - Amirov, S. M.; Ramazanov, T. S.; Moldabekov, Zh. A. (21st International Symposium on Heavy Ion Inertial Fusion. Autonomous Organization of Education “Nazarbayev University”, 2016)
In this paper we consider the effective potential of interaction between ions in quantum plasmas. Effective interaction potential, taking into account the wave nature of ion at small interparticle distances can be obtained by the method of the dielectric response function in combination with so called quantum potential approach...
Keywords: ions; quantum; Research Subject Categories::NATURAL SCIENCES::Physics::Elementary particle physics